2020
DOI: 10.1007/s00167-020-06141-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute, isolated and unstable syndesmotic injuries are frequently associated with intra-articular pathologies

Abstract: Purpose Although simultaneous arthroscopy for the surgical treatment of acute isolated, unstable syndesmotic injuries has been recommended, little knowledge is present about the actual frequency of intra-articular pathologies for this injury. The aim of this study was to investigate the frequency and severity of intra-articular pathologies detected during arthroscopy and their subsequent treatment in acute isolated, unstable syndesmotic injuries. Methods A retrospective chart review of patients treated by arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
(67 reference statements)
0
25
1
2
Order By: Relevance
“…As concluded by Mankin et al in 1974, if superficial lacerations of articular cartilage are limited in size and depth, they will ‘ neither heal nor progress to more serious disorders ’ [ 16 , 17 ]. This statement can be substantiated by a recent meta-analysis that showed that although the incidence of reported osteochondral damage after ankle sprain or fracture was high (namely 45%), the proportion that may result in poor clinical outcomes (as a consequence of osteochondral damage or end-stage osteoarthritis) can be considered relatively low [ 5 , 19 , 26 , 33 , 37 ]. This finding has further been described by several studies reporting good patient-reported mid- to long-term outcomes following ankle trauma (sprains and fractures) [ 11 , 12 ].…”
Section: Asymptomatic Superficial Cartilage Lesionsmentioning
confidence: 99%
“…As concluded by Mankin et al in 1974, if superficial lacerations of articular cartilage are limited in size and depth, they will ‘ neither heal nor progress to more serious disorders ’ [ 16 , 17 ]. This statement can be substantiated by a recent meta-analysis that showed that although the incidence of reported osteochondral damage after ankle sprain or fracture was high (namely 45%), the proportion that may result in poor clinical outcomes (as a consequence of osteochondral damage or end-stage osteoarthritis) can be considered relatively low [ 5 , 19 , 26 , 33 , 37 ]. This finding has further been described by several studies reporting good patient-reported mid- to long-term outcomes following ankle trauma (sprains and fractures) [ 11 , 12 ].…”
Section: Asymptomatic Superficial Cartilage Lesionsmentioning
confidence: 99%
“…There were 63 talar lesions (95.4%) and 3 tibial lesions (4.5%). One study 5 reported on a specified sub-localization distribution of the lesions, and these results can be appreciated in Table 3 . Lesion size was not reported in any of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The overall pooled incidence rate of (osteo)chondral lesions in the ankle joint in all isolated syndesmotic injuries—acute and chronic group combined—was 20.7% (95% CI: 13.7%-29.9%) as there were 79 reported lesions in a total of 402 patients ( I 2 = 65%) 4 , 5 , 21 - 27 ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passage of a 3 mm spherical probe during external rotation indicates very high likelihood of rupture of both the AITFL and the IOL, 48 against previous reports classifying unstable lesions when diastasis was greater than 2 mm. Additionally, half of these lesions can present with concomitant intra-articular pathologies (osteochondral lesions, other ligamentous rupture or loose bodies) with 19% needing additional treatment, 49 reinforcing the role of arthroscopy not only for diagnosis but also for concomitant treatment. It is also an excellent tool to evaluate anatomic reduction and residual diastasis.…”
Section: Syndesmosis Instabilitymentioning
confidence: 99%